The statistical implications of pre-test and Stein-rule estimators in econometrics - Judge, George G.; Bock, M. E.; Theil, Henri (Amsterdam ; New York : North-Holland Pub. Co., 1978)
In this book the authors look within a decision theory context with the statistical consequences of using a range of traditional and non-traditional estimation rules when knowledge of the economic processes and institutions by which the data are generated is incomplete and therefore the economic and statistical sampling models are incorrectly or incompletely known.
Includes index.
Includes bibliographical references: p. 331-338.
rpm 25/09/2017
Loans
Keywords: Econometrics; Estimation theory; Monte Carlo method